A monthly stock exchange index for Ireland, 1864-1930 - Grossman, RS; Lyons, RC; O'Rourke, KH; Ursu, MA (University of Oxford, 2013)
Information on the performance of equities during the latter part of the globalized long nineteenth century is scarce, particularly for smaller European economies such as Ireland. Using a dataset of over 35,000 price-year observations from the Investor's Monthly Manual, this paper constructs new monthly Irish stock market price indices for the period 1864-1930, encompassing periods of significant economic and political turmoil in Irish history. In addition to a total market index covering all 118 equity securities issued by 94 companies, sector-specific indices are presented for railways, financial services companies, and miscellaneous industrial and retail companies. Weighted by market capitalization, nominal equity prices were largely static in the 1860s, before increasing by almost 60% in nominal terms between 1870 and 1878. Between 1878 and 1879, equity prices fell by one sixth in the space of a year, after which there was a secular rise in equity prices for two decades, with equity prices in 1899 twice what they had been in 1864. Between the turn of the century and the outbreak of the Great War, though, prices fell by 25%, a pattern that stands in stark contrast to returns on the London exchange, which were greater during 1894-1913 than during the preceding two decades. The period from 1914 until 1929 saw a number of boom-bust cycles, concurrent with war and other political events affecting Ireland, including its independence movement. Railway equities, which had trebled between the mid-1860s and the turn of the century, fell sharply during the 1910s and 1920s. In contrast, financial equity prices - which were just 20% higher in 1920 than in 1864 - rose strongly during the 1920s. Overall, the average annual gain in equity prices over the period was just 0.9%, well below levels associated with an equity premium puzzle.